A Traditional Chinese Herb Citri Reticulatae Pericarpium Induced Melanonychia - Jiang S; Xu J; Xiong X; Deng Y (Dove Medical Press, 2022)
Shiyu Jiang, Jixiang Xu, Xia Xiong, Yongqiong Deng Department of Dermatology & STD, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of ChinaCorrespondence: Yongqiong DengDepartment of Dermatology & STD, The Affiliated Hospital of Southwest Medical University, No. 25, Taiping Street, Luzhou, 646000, Sichuan Province, People's Republic of ChinaTel +86-13679670608Fax +86-8303165651Email dengyongqiong1@126.comAbstract: The common causes for melanonychia include melanoma, repetitive trauma, underlying systemic diseases, onychomycosis, pseudomonas infection and drugs. Drug-induced melanonychia usually affects numerous nails and appears as light brown to black pigmentation on the deck or nail bed with longitudinal, transverse or diffuse distribution. In previous cases, a number of chemotherapeutic agents such as azathioprine, bleomycin sulfate, cyclophosphamide, hydroxyurea and methotrexate were usually linked to melanonychia. Citri reticulatae pericarpium (CRP) is a traditional Chinese herb which is widely used in many foods and health care products in China. Up till now, there were no adverse reactions of CRP reported throughout the literature. Herein, we firstly reported a case of melanonychia in a 67-year-old man caused by CRP for external use.Keywords: traditional Chinese herb, citri reticulatae pericarpium, melanonychia